Effect of sandwich compost leachate on allium tuberosum seed germination - Chooi, Lin Phooi; Azman, Elisa Azura; Ismail, Roslan; Shahruddin, Shafeeqa (Universiti Putra Malaysia Press, 2022)
Food waste is a serious global issue, and one way to reduce the impact of food waste is by composting. Sandwich compost is a type of fermented food waste compost created with microbial fermentation; meanwhile, the composting leachate provides nutrients for plants. Studies have shown that seed germination may be enhanced when treated with sandwich compost leachate. Furthermore, few studies have been on sandwich compost leachate used for seed priming. The objective of this study was to determine the effect of varying leachate concentrations of food waste sandwich compost and priming durations on the performance of Chinese chive (Allium tuberosum) seed germination. Chinese chive (Allium tuberosum) was chosen as the test crop. It is widely used as a flavouring herb with high economic potential; however, its seed germination time is long and requires pre-treatment such as crushing and seed priming to speed up the germination process. The study used four replications and a complete randomisation design (CRD). The seeds were exposed to different percentages of sandwich compost leachate (0.0%, 0.2%, 0.4%, 0.6%, 0.8%, and 1.0%) and priming duration (4, 8, and 12 hours). A significant interaction between the bio-nutri-priming concentration and priming duration was demonstrated by measuring the standard error of germination rate (( ) and ) corrected germination rate index (Scorrected). A longer bio-nutri-priming duration was key for a higher seed vigour index. The bio-nutripriming concentration and priming duration, however, had no significant interaction.Longer bio-nutri-priming durations were recommended to obtain better germination performance of Chinese chive. The study showed that a twelve-hour bio-nutri-priming duration and a 0.6 % leachate concentration significantly enhanced the Chinese chive seed germination and helped break seed dormancy.